2011
DOI: 10.1093/hmg/ddr042
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor FOXL2 protects granulosa cells from stress and delays cell cycle: role of its regulation by the SIRT1 deacetylase

Abstract: FOXL2 is a transcription factor that is essential for ovarian function and maintenance, the germline mutations of which are responsible for the Blepharophimosis Ptosis Epicanthus-inversus Syndrome (BPES), often associated with premature ovarian failure. Recent evidence has linked FOXL2 downregulation or somatic mutation (p.Cys134Trp) to cancer, although underlying molecular mechanisms remain unclear. Using a functional genomic approach, we find that FOXL2 modulates cell-cycle regulators in a way which tends to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 61 publications
4
65
0
2
Order By: Relevance
“…Differences have been found between wild-type and mutant FOXL2 however, such as increased induction of the target aromatase by the mutation [53] and a lower capacity of the mutation to induce apoptosis, thereby compromising cell death [47,48,53]. A very recent study by Benayoun et al [54] suggested that this mutation might interfere with the capacity of FOXL2 to modulate the cell cycle.…”
Section: Foxl2 Impairment In Granulosa Cell Tumorsmentioning
confidence: 99%
“…Differences have been found between wild-type and mutant FOXL2 however, such as increased induction of the target aromatase by the mutation [53] and a lower capacity of the mutation to induce apoptosis, thereby compromising cell death [47,48,53]. A very recent study by Benayoun et al [54] suggested that this mutation might interfere with the capacity of FOXL2 to modulate the cell cycle.…”
Section: Foxl2 Impairment In Granulosa Cell Tumorsmentioning
confidence: 99%
“…A recurring somatic mutation in this gene has been described as a potential 'driver' in the pathogenesis of adult-type GCTs [7]. A few studies have investigated the effect of the mutant allele, including studying its transcriptional targets [8][9][10][11][12]. The identification of a recurring mutation reported to be present in up to 94-97% of adult-type tumours may serve as another diagnostic tool for GCTs, alongside traditional pathological and immunohistochemical features.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that SIRT1 protein was expressed in mouse ovarian tissues (Morita et al, 2012), human luteinized granulosa cells (Benayoun et al, 2011) and bovine oocytes (Ghinis-Hozumi et al, 2011). The present study showed that SIRT1 protein was widely expressed in porcine ovary.…”
Section: Discussionmentioning
confidence: 99%